Studying the Effect of Changing the Security Techniques Used in the MS-LEACH Protocol on the Energy Consumed in WSN Networks - ليلى, إناس; الخطيب, حلا (Latakia University Journal -Engineering Sciences Series, 2020)
Wireless sensor networks are pioneers in the field of technology, and it's being focused on employing them in different fields, it will also be the foundation stone of Internet Of Things (IOT). And data collected in some WSN applications may need to be confidential and arrive at its destination properly, and this is a major challenge in WSN due to its limited resources such as energy and computational capabilities, which makes finding appropriate protection mechanisms a difficult task. Symmetric cryptographic algorithms such as RC5, AES, and Skipjack are more suited for secrecy than asymmetric cryptographic algorithms, as they are faster to implement and less complicated in calculations. And CBC-MAC and HMAC technologies are also among the most important message integrity and sending node identity verification technologies. In this research, we first evaluated the performance of the two secure hierarchical protocols SecLEACH and MS-LEACH in the steady-state phase, We implemented scenarios using MatLab, and we used two main metrics to evaluate performance: residual power and the number of alive nodes in the network. The results showed that the SecLEACH protocol is less energy consuming than the MS-LEACH protocol, but this protocol does not guarantee the confidentiality of the transmitted data, while the MS-LEACH protocol ensures that which results in consuming more energy compared to SecLEACH. We then studied the effect of applying a range of security technologies such as RC5, Skipjack and HMAC in the MS-LEACH protocol in order to improve the energy efficiency of the network, and the results showed that the use of the Skipjack encryption algorithm and the HMAC authentication algorithm in the MS-LEACH protocol prolonged the network life and improved energy efficiency.